Effect of loading rate on inter laminar shear strength (ILSS) of highly doped MWCNTs carbon/epoxy laminates. (December 2018) - Kumar, Chandan; Singh, K.K.; Rawat, Prashant; Deep, Akash; Behera, Rohit Pratyush
Abstract: The present experiment investigates the sensitivity of strain rate on mechanical properties of MWCNTs (multi-walled carbon nanotubes) reinforced carbon woven composites. The SBS (short beam strength) tests were done to evaluate the dependence of strain rate on ILSS (inter laminar shear strength) of prestine neat and 1, 2, 3 and 4 wt. % MWCNTs doped CFRP (carbon fiber reinforced polymer). The symmetrical bi-directional carbon fiber laminate comprising of eight layers with 0.5 mm thickness each and ply orientation of [(0, 90) / (+45, -45) / (+45, -45) / (0, 90)]S was designed. The laminates were prepared by hand lay-up method assisted by vacuum bagging technique. The prepared laminates were cut using the diamond cutter and the obtained samples were tested on H50KS, the UTM (universal testing machine) as per ASTM D2344. Three different loading rates of 1, 110 and 220 mm/min were used to see the mechanical performance of CFRP with no doping and with doping of higher percentage by weight of MWCNTs. The results revealed strain rate dependency of carbon/epoxy laminates on its mechanical performance. In the test, 3 wt. % MWCNTs doped CFRP showed maximum shear strength at the strain rate of 110 mm/min. Also, FEA (finite element analysis) using ANSYS were done and the results were found to be in good agreement with the experimental data.